New moss records from western part of Turkey (Bangladesh Journal of Botany, 2014)
Two species of moss namely, Onchoporus dendrophilus Hedderson & Blockeel and Sphagnum fimbriatum Wilson are reported for the first time from Turkey. Onchoporus dendrophilus is also a new report from Southwest Asia. Diagnostic characters, descriptions and illustrations were studied. DOI: http://dx.doi.org/10.3329/bjb.v42i2.18047 Bangladesh J. Bot. 42(2): 371-375, 2013 (December)